Spectroscopic study of the diameter distribution of B-doped single-walled carbon nanotubes - G. Ruiz-Soria (2018)
In this paper, we report on the diameter distribution of boron-doped single-walled carbon nanotubes grown from triethyl borate with high vacuum chemical vapor deposition, using multi-frequency Raman resonance spectroscopy. The nanotube yield is higher than in previously reported material produced with the same method. Our results suggest that the amount of as-grown material and the range of diameters are directly correlated with feedstock used in the synthesis. The ID/IG ratio shows that the morphology of the samples is critically affected by the temperature. The population of diameters in the optimal conditions shows a Poisson distribution with a mean value at ∼1.15nm. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.